Prevalence of Gastroesophageal Reflux Disease and Its Risk Factors In Rural Area - Florentina Caroline Puspita; Leonita Ariesti Putri; Cindy Rahardja; Amanda Pitarini Utari; Ari Fahrial Syam (The Indonesian Society for Digestive Endoscopy, 2017)
Background: Prevalence of gastroesophageal reflux disease (GERD) is escalating in Asia. The present study aimed toinvestigate the prevalence of GERD symptoms as well as potential risk factors associated with GERD in residents in a rural area in Jakarta. Method: The study population consisted of subjects who aged 20 years or more and lived in rural area Kebon Bawang-Tanjung Priok, Jakarta. A self-administered questionnaire based on earlier validated questionnaire (GERDQ) was given. The questionnaire consisted of demographic characteristic, self and environment sanitary, social and past illness history, and the symptoms score for GERD. Total score for GERD’s symptoms score was 18, with a score of at least 8 was considered to have symptomatic GERD.Results: The questionnaire was completed in 90 subjects. Of the 90 subjects, 12 (13.3%) had GERDQ score ≥ 8 which was the cut-off for definingpresence of GERD. On both univariate and multivariate analysis, age 50 years old (OR = 6.33; 95% CI 1.1-35.6), handwashing habit before eating (OR = 6.93; 95% CI 1.1-43.8), and raw/tap water (OR = 10.28; 95% CI 0.8-130) were significantly associated with the presence of GERD.Conclusion: Prevalence of GERD was high (13.3%) in rural area in Jakarta. Age 50 years old, handwashing habit before eating, and raw/tap waterwere risk factors for GERD in this population.